STOCKLIST—A STUDY OF CLINICAL SKILLS OF CRITICAL CARE PARAMEDICS IN THE UK. Issue 5 (18th April 2015) - Walmsley, Jim; Turner, Janette
Abstract : Introduction: The Critical Care Paramedic (CCP) is a relatively new advanced practitioner. CCPs provide advanced clinical skills, knowledge and expertise for primary response and critical care retrieval and transfer. In the UK it is currently an undefined role with no common code of practice, clinical governance or national guidance. The aim of this study was to explore the current use of CCPs and assess the views of a range of stakeholders on the required skills and role development within a British context. Methods: A web based survey design was used to collect information on CCP use and views on skills, role and scope of practice. The survey asked questions on current or intended use of CCPs and skills used. Respondents were asked to rate a list of 23 clinical skills on whether they were essential, desirable or irrelevant; importance of a set of standards and statements about the role of CCPs in the ambulance service. Stakeholders approached included ambulance services, professional bodies, charitable organisations and academic departments. Results: From 198 invitations there were 141 responses (70%) and 70% were from ambulance trusts. Half of responders said they currently used CCPs. The top 5 essential skills were concerned with airway management. Views on core standards and the CCP role are summarised in the table. Conclusions: The survey confirmed the CCP role is currently undefined and used variably in practice. There was agreement on the need for core skills and standards but the nature of these is still a matter for debate.